Impact of Macroeconomic Variables on Stock Market Performance: The Case of Karachi Stock Exchange - SAEED AKBAR; DR. ZAHOOR-UL-HAQ (Journal of Business & Tourism, 2021)
The aim of this paper is to analyze the impact of key macroeconomic variables on stock market performance. These variables include Gross Domestic Product (GDP), interest rate, inflation rate, exchange rate, money supply (M2), Foreign Direct Investment (FDI), and use of IMF credit. The dependent variable is the market capitalization of Karachi Stock Exchange. The results of co-integration confirmed a long-run co-integrating relationship between the selected macroeconomic variables and stock market performance. Furthermore, the Vector Error Correction Model was applied which showed a long-run equilibrium relationship between macro variables and stock market performance but it failed to established any short-run relationship. The results of TodaYamamoto Causality test confirmed a uni-directional causality from market capitalization to GDP and interest rate only but no causality was found from any variable to market capitalization. So it is concluded that the macroeconomic variables do form a relationship with the stock market performance in the long-run but no such relationship was found in the short-run and hence Karachi Stock Exchange cannot be regarded as a leading indicator of Pakistan’s economy.